2019
DOI: 10.1038/s41467-019-08899-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast energy relaxation dynamics of amide I vibrations coupled with protein-bound water molecules

Abstract: The influence of hydration water on the vibrational energy relaxation in a protein holds the key to understand ultrafast protein dynamics, but its detection is a major challenge. Here, we report measurements on the ultrafast vibrational dynamics of amide I vibrations of proteins at the lipid membrane/H 2 O interface using femtosecond time-resolved sum frequency generation vibrational spectroscopy. We find that the relaxation time of the amide I mode shows a very strong dependence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 67 publications
0
54
0
Order By: Relevance
“…There is a consensus that dynamic nanoscopic heterogeneities are involved in signal transduction in biological membranes (65). Recently, it was shown that the collective picosecond dynamics of interfacial water (with the energy range of 2 to 5 meV) can serve as a relaxation pathway for protein backbones (66,67). Therefore, it is intriguing that the ultrafast dynamics of functional lipid pairs (the energy of the optical modes) operate at the same timescales as relaxation processes of the transmembrane proteins (66).…”
Section: Discussionmentioning
confidence: 99%
“…There is a consensus that dynamic nanoscopic heterogeneities are involved in signal transduction in biological membranes (65). Recently, it was shown that the collective picosecond dynamics of interfacial water (with the energy range of 2 to 5 meV) can serve as a relaxation pathway for protein backbones (66,67). Therefore, it is intriguing that the ultrafast dynamics of functional lipid pairs (the energy of the optical modes) operate at the same timescales as relaxation processes of the transmembrane proteins (66).…”
Section: Discussionmentioning
confidence: 99%
“…294 The Ye group investigated the impact of hydration water on the vibrational energy relaxation in an interfacial protein. 247 Tan et al probed the vibrational dynamics of the amide-I mode of the KALP23 peptide at the H 2 O and D 2 O interface. The vibrational relaxation times showed a strong solvent dependence that the authors attributed to resonant vibrational energy transfer from the amide-I mode to water bending modes.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Here, the main purpose of the switch is to activate the molecules [ 27 ] which experience the relaxation time as a response to the continuous wave (CW) on the femtosecond timescale. [ 28 ] Here, we report for the first time the time‐dependent absorption of the NMA molecules. Time‐dependent absorption of other molecules is known and was reported for instance in ref.…”
Section: Introductionmentioning
confidence: 99%